Factores que inciden en la Rentabilidad de las Cooperativas de Ahorro y Crédito del segmento dos Periodo 2019-2020 - Cueva Jiménez, Neusa Cecilia (2022)
Financial Cooperatives play a relevant role in the national economy by having financial intermediation as their main activity, generating an economic return. Thus, the internal and external factors that affect the profitability of savings and credit cooperatives belonging to segment two in the city of Loja were analyzed. This work was developed by grouping indicators considered as three-dimensional internal factors, which were evaluated using the methodology of indicators given by the Superintendency of Popular and Solidarity Economy, PERLAS and CAMEL, and external factors were analyzed and evaluated qualitatively to identify the impact on profitability. Results show that the three dimensions of internal factors do not affect profitability; however, when analyzing each cooperative in the dimension of efficiency and productivity, the CACEL Cooperative was affected in terms of profitability. Regarding the external variables, GDP does not affect profitability, while the tax burden and the interest rate affect profitability. In summary, financial cooperatives must constantly identify the factors that affect their economic profitability, but without neglecting social profitability, which must be the overriding aspect in the management of saving and credit cooperatives. This fulfills the purpose of creation and what is established by the Organic Law of Popular and Solidarity Economy to promote the common benefit.